Data-Driven Innovation in Smart Manufacturing:A Systematic Review of Predictive Decision-Making and Industrial Optimization - Adinda Ludwika; Fathan Dewadi; Fadli Robbi; Abel Sulaiman (JADI (Jurnal Teknik Industri), 2026)
Industry 5.0 has accelerated the transformation of manufacturing industries toward autonomous, intelligent, and human-centric production systems. Smart manufacturing technologies increasingly integrate Artificial Intelligence (AI), Internet of Things (IoT), Digital Twin, and Cyber-Physical Systems (CPS) to support predictive decision-making and industrial optimization. This study aims to analyze the development of autonomous smart manufacturing systems through a systematic literature review approach. The review process followed the PRISMA methodology using publications indexed in Scopus, Web of Science, and Google Scholar from 2016–2026. The results indicate that AI-driven manufacturing systems improve predictive maintenance, operational efficiency, production flexibility, and industrial sustainability. However, challenges related to cybersecurity, infrastructure readiness, implementation costs, and ethical AI governance remain significant barriers. This study concludes that autonomous smart manufacturing systems possess strong potential to support intelligent and sustainable industrial transformation in the Industry 5.0 era.